2003
DOI: 10.1073/pnas.2034961100
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule destabilization and nuclear entry are sequential steps leading to toxicity in Huntington's disease

Abstract: There has been a longstanding debate regarding the role of proteolysis in Huntington's disease. The toxic peptide theory posits that N-terminal cleavage fragments of mutant Huntington's disease protein [mutant huntingtin (mhtt)] enter the nucleus to cause transcriptional dysfunction. However, recent data suggest a second model in which proteolysis of full-length mhtt is inhibited. Importantly, the two competing theories differ with respect to subcellular distribution of mhtt at initiation of toxicity: nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 37 publications
5
67
0
Order By: Relevance
“…9C). Thus, consistent with a previous report (34), chemicallystabilized microtubules protected against detrimental stress stimuli.…”
Section: Jnk Signaling To Stmn Regulates Protection Against Cellular supporting
confidence: 93%
See 1 more Smart Citation
“…9C). Thus, consistent with a previous report (34), chemicallystabilized microtubules protected against detrimental stress stimuli.…”
Section: Jnk Signaling To Stmn Regulates Protection Against Cellular supporting
confidence: 93%
“…The depolymerization of the microtubule network is also recognized as an early event in apoptosis execution, and loss of microtubules can initiate cell death (33,34). Thus, we investigated the contribution of microtubule stabilization to cell responses to stress.…”
Section: Jnk Signaling To Stmn Regulates Protection Against Cellular mentioning
confidence: 99%
“…Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003). Nanomolar concentrations of paclitaxel can protect neurons against various toxic insults and enhance survival by maintaining Ca 2+ homeostasis (Burke et al 1994;Furukawa and Mattson 1995;Furukawa et al 2003;Sponne et al 2003;Michaelis et al 2005) without evidence of toxicity (Trushina et al 2003). Our study demonstrates that tau is not phosphorylated by MTstabilizing/destabilizing drugs at lower doses, but it is phosphorylated at higher doses.…”
Section: Discussionmentioning
confidence: 59%
“…In support of this, we recently reported that Taxol prevents the early reactive oxygen species-dependent cytoskeletal perturbation and the subsequent neuronal apoptosis induced by soluble A␤ (17). Destabilization of the microtubule network as a primary and main actor of neurotoxicity induced by various toxic peptides has also been described in other pathologies such as Huntington disease (47).…”
Section: Discussionmentioning
confidence: 66%